Roomies for Life? An Assessment of How Staying with a Local Facilitates Refugee Integration. Issue 3 (3rd July 2022) - van Dijk, Hans; Knappert, Lena; Muis, Quita; Alkhaled, Sophie
Abstract: In light of failing integration policies and practices, we provide a qualitative evaluation of a social innovation that aims to facilitate integration by providing refugees an opportunity to reside temporarily with locals. Our analysis of the experiences shared by refugee guests and local hosts provides insight on the theory and practice of refugee integration in three ways: we (1) inform research and policy on the effectiveness of staying with a local as a means for integrating refugees, (2) unpack the mechanisms through which staying with a local facilitates refugee integration, and (3) theoretically enrich the literature on indicators of integration.